THE IDEOLOGY OF MINORITY: A TRANSNATIONAL STUDY OF THE AMERICAN NEW LEFT IN 1960S - Kidhot Kasjuaji (Rubikon : Journal of Transnational American Studies, 2015)
Student organizations have been acknowledged as vanguards and agents of social and political change in some parts of the world. In America, the dynamic student organizations cannot be set apart from American history. The upheaval of the 1960s signaled the advent of the New Left movement, comprising the Free Speech Movement (FSM) and Students for A Democratic Society (SDS). While, in the Indonesian experience, there was somewhat of a similarity of thought and spirit related with the role of student movements historically. Therefore, the study is intended to discover the emergence of the New Left in Europe and America, and expose the cultural hybridity-similarities and reasons of occurrence-of the American New Left and Indonesian student movement in the 1970s. This research is written under the American Studies discipline, specifically related to Transnational American Studies by employing cultural hybridity and border discourse. The finding shows that the ideology of the American New Left in the 1960s comprises of a means of globalizing the New Left in Europe and America, involving the universal ideas of inequality, communication, people migration, and social phenomena in the 1960s and the cultural hybridity of the ideology of the American New Left in the 1960s and the Indonesian student movement of the 1970s evidently showing that the New Left is a ‘third ideology’ by resisting two globalized ideologies during the 1960s, capitalism and communism. In addition, the locality or sustained values, which are democracy and social justice and the universal values shared of the American New Left, FSM and SDS, and the Indonesian student movement in the 1970s are anti-establishment and anti-capitalistic society.Keywords: New Left, ideology, cultural hybridity, border discourse, minority.